2004
DOI: 10.1073/pnas.0403303101
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory potential and control ofFoxp3expression in newborn CD4+T cells

Abstract: Thymectomy at day 3 after birth leads to autoimmune disease in some genetic backgrounds. Disease is thought to be caused by the lack͞paucity of regulatory T cells. We show that 3-day-old mice already contain a significant compartment of Foxp3-expressing CD25 ؉ CD4 ؉ splenocytes. Whereas, in adult spleen, the subsets of regulatory T cells (CD25 ؉ and͞or CD103 ؉ ) express high amounts of Foxp3 mRNA, in 3-day-old mice, both thymic and splenic CD25 ؉ CD4 ؉ T cell subsets express lower amounts of Foxp3 mRNA, and CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
65
2
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 51 publications
9
65
2
2
Order By: Relevance
“…Our findings confirm the observations of Dujardin et al (12); in d3tx mice, functional Treg, now identified as Foxp3 ϩ CD4 ϩ T cells, are persistently increased relative to the CD25 Ϫ effector T cells. To extend the study, we investigated the in vivo function of Treg in d3tx mice, in particular their capacity to influence autoimmune diseases that develop in d3tx mice (5).…”
Section: Foxp3 ϩ Cd4 ϩ T Cells Are Increased In the Ln And Target Orgsupporting
confidence: 93%
See 4 more Smart Citations
“…Our findings confirm the observations of Dujardin et al (12); in d3tx mice, functional Treg, now identified as Foxp3 ϩ CD4 ϩ T cells, are persistently increased relative to the CD25 Ϫ effector T cells. To extend the study, we investigated the in vivo function of Treg in d3tx mice, in particular their capacity to influence autoimmune diseases that develop in d3tx mice (5).…”
Section: Foxp3 ϩ Cd4 ϩ T Cells Are Increased In the Ln And Target Orgsupporting
confidence: 93%
“…Pivotal support for the Treg-depletion hypothesis of d3tx disease was provided by the reported late ontogeny of Treg development (9, 10), but the supporting data are controversial (10,12). More importantly, there has not been an attempt to investigate the in vivo function of neonatal Treg, specifically their capacity to suppress the autoimmune disease of the d3tx mice.…”
Section: Three-day-old Neonatal Mice Possess Functional Cd4 ϩ Cd25 ϩ mentioning
confidence: 99%
See 3 more Smart Citations